2001
DOI: 10.1038/ncb0901-856
|View full text |Cite
|
Sign up to set email alerts
|

Enteropathogenic E. coli Tir binds Nck to initiate actin pedestal formation in host cells

Abstract: Enteropathogenic Escherichia coli (EPEC) is a bacterial pathogen that causes infantile diarrhea worldwide. EPEC injects a bacterial protein, translocated intimin receptor (Tir), into the host-cell plasma membrane where it acts as a receptor for the bacterial outer membrane protein, intimin. The interaction of Tir and intimin triggers a marked rearrangement of the host actin cytoskeleton into pedestals beneath adherent bacteria. On delivery into host cells, EPEC Tir is phosphorylated on tyrosine 474 of the intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
388
1
2

Year Published

2003
2003
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(401 citation statements)
references
References 25 publications
10
388
1
2
Order By: Relevance
“…62 and 63). We show here that in T cells, as in shigella, vaccinia, and EPEC (41,42,64), Nck is a component of the WASP/N-WASP signaling complex. The recruitment of Nck to tyrosine phosphorylation sites in SLP-76 parallels the recruitment of Nck to tyrosine phosphorylated sites in the Tir protein of EPEC (42,65) and in the A36R protein of vaccinia (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 and 63). We show here that in T cells, as in shigella, vaccinia, and EPEC (41,42,64), Nck is a component of the WASP/N-WASP signaling complex. The recruitment of Nck to tyrosine phosphorylation sites in SLP-76 parallels the recruitment of Nck to tyrosine phosphorylated sites in the Tir protein of EPEC (42,65) and in the A36R protein of vaccinia (41).…”
Section: Discussionmentioning
confidence: 99%
“…We show here that in T cells, as in shigella, vaccinia, and EPEC (41,42,64), Nck is a component of the WASP/N-WASP signaling complex. The recruitment of Nck to tyrosine phosphorylation sites in SLP-76 parallels the recruitment of Nck to tyrosine phosphorylated sites in the Tir protein of EPEC (42,65) and in the A36R protein of vaccinia (41). In T cells, we find that Nck functions to recruit WASP, just as Nck is required to recruit N-WASP to the vaccinia virus particle (39,41) and to the EPEC pedestal (42).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations revealed that binding of intimin with Tir results in the phosphorylation of Y474 (26) and that the phosphorylation is required for the recruitment and clustering of the host adaptor protein Nck beneath the attached bacterium and for the subsequent activation of the N-WASP-Arp2/3 pathway (19,23). As a result, neither ZO-1 accumulation nor actin polymerization was observed with the ⌬ tir mutant expressing Tir(Y474F), whereas the ⌬ tir mutant expressing a wild-type Tir caused both the accumulation and the formation of pedestals (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The secreted Tir is in turn integrated into the plasma membrane and binds with a bacterial outer membrane protein, intimin (31). The binding induces the clustering of the membrane-associated Tir beneath the bacteria, which activates an Nck adaptor molecule at the cytoplasmic face of the plasma membrane and finally results in activation of neural Wiskott-Aldrich syndrome protein (N-WASP) and the downstream actin-nucleating Arp2/3 complex (19,23). Actin polymerization induced by S. flexneri is mediated by a bacterial outer membrane protein, IcsA/VirG (5).…”
mentioning
confidence: 99%
“…The consequence of this difference is that EPEC Tir recruits the host protein Nck to the pedestal, while EHEC Tir does not. The specificity of this interaction was recently narrowed to a 12-amino-acid region including Y474 (1,15). Two other signaling molecules, Grb2 and CrkII, are recruited only to EPEC pedestals but not to EHEC pedestals (reviewed in reference 2).…”
Section: Discussionmentioning
confidence: 99%